Factors affecting retirement planning behaviour among working adults in the private sector: the case of Pulau Pinang, Kuala Lumpur, and Johor. - Chong, Heng Xu; Chow, Whye Shing; K. Vasu, Divya Sri (2023)
Retirement planning behaviour is a crucial practice for retirement savings to safeguard one’s post-retirement life quality. This study focuses on assessing the influence of inadequate retirement planning behaviour on retirement savings. Therefore, the study investigates the relationship between retirement planning behaviour and factors, including family education, financial literacy, and goal clarity in the context of working adults in the private sector since they do not have any pension schemes but merely EPF contributions. As a result, this study is particularly centered on working adults employed in the private sector, who have been more vulnerable and mostly affected among the working population. A total of 411 surveys had been gathered from regions, including Kuala Lumpur, Pulau Pinang, and Johor. Subsequently, Statistical Package for the Social Sciences (SPSS) version 27.0 was employed for data analysis. Several tests were performed, such as reliability test, consistency test as well as multiple linear regression analysis. The results of the data analysis showed that financial literacy and goal clarity had significant influences on retirement planning behaviour. However, family education is reported to be insignificantly related to retirement planning behaviour. Thus, the implications are recommended to all relevant institutions with the purpose of promoting education among individuals to enhance their retirement planning behaviour.